Effects of [Asu1, 7]-eel calcitonin on gastric somatostatin and gastrin release. Issue 2 (February 1980) - Chiba, T; Taminato, T; Kadowaki, S; Goto, Y; Mori, K; Seino, Y; Abe, H; Chihara, K; Matsukura, S; Fujita, T; Kondo, T
Abstract : Effects of [Asu1, 7]-eel calcitonin on gastric somatostatin and gastrin secretion were studied by using the isolated perfused rat stomach. [Asu1, 7]-eel calcitonin (10(-9)--10(-7)M) caused a simultaneous dose-dependent increase of gastric somatostatin release and decrease of gastrin secretion, with a significant correlation between these two. The demonstration of calcitonin stimulation of gastric somatostatin release raises the possibility of somatostatin-mediated suppression of gastrin secretion by calcitonin.